A 2-Year-Old Victim of an MVA - Kathleen Ventre (Association of American Medical Colleges, 2010)
Abstract Introduction This resource contains as simulation that represents a previously well 2-year-old presenting to the emergency department following a motor vehicle accident. Methods During the simulation, participants learn that the child was responsive at the scene but became confused and weak as she entered the emergency department (ED). At the time of initial ED assessment she is unresponsive. This child is apneic, with a narrow complex rhythm and unobtainable blood pressure. Participants must recognize pulseless electrical activity and treat aggressively by offering prompt and sustained CPR, epinephrine every 3-5 minutes, and 40 cc/kg in intravenous fluid boluses. Results During the usability testing conducted at our institution, 95% of individuals who completed the pediatric advanced life support cases on a computer simulator felt that it was an effective training experience. Discussion Our institution has a full-scale mannequin simulator laboratory with a curricular focus on interdisciplinary, team-based management of pediatric medical emergencies. The majority of providers in our hospital who regularly train in the mannequin laboratory use these computer scenarios to prepare for their team training, and the vast majority of these individuals feel it prepares them to better succeed during their team training exercises.